Posterior cortical atrophy: visuomotor deficits in reaching and grasping - Meek, Benjamin P.; Shelton, Paul A.; Marotta, Jonathan J. (Frontiers in Human Neuroscience, 2013)
Posterior Cortical Atrophy (PCA) is a rare clinical syndrome characterised by the predominance of higher-order visual disturbances such as optic ataxia, a characteristic of Balint’s syndrome. Deficits result from progressive neurodegeneration of occipito-temporal and occipito-parietal cortices. The current study sought to explore the visuomotor functioning of four individuals with PCA by testing their ability to reach out and grasp real objects under various viewing conditions. Experiment 1 had participants reach out and grasp simple, rectangular blocks under visually- and memory-guided conditions. Experiment 2 explored participants’ abilities to accurately reach for objects located in their visual periphery. This investigation revealed that PCA patients demonstrate many of the same deficits that have been previously reported in other individuals with optic ataxia, such as ‘magnetic misreaching’ – a pathological reaching bias towards the point of visual fixation when grasping peripheral targets. Unlike many other individuals with optic ataxia, however, the patients in the current study also show symptoms indicative of damage to the more perceptual stream of visual processing, including abolished grip scaling during memory-guided grasping and deficits in face and object identification. These investigations are the first to perform a quantitative analysis of the visuomotor deficits exhibited by patients with Posterior Cortical Atrophy. Critically, this study helps characterize common symptoms of PCA, a vital first step for generating effective diagnostic criteria and therapeutic strategies for this understudied neurodegenerative disorder.